Compost quality and markets are pivotal for sustainability in circular food-nutrient systems: a case study of Sri Lanka - Roy, E. D.; Esham, M.; Jayathilake, Nilanthi; Otoo, M.; Koliba, C.; Wijethunga, I. B.; Fein-Cole, M. J. (Frontiers Media, 2021)
Sustainable management of municipal solid waste (MSW) is a critical issue around the world, especially in South Asia where waste generation is expected to double by 2050. Closing the food-nutrient cycle through composting biodegradable MSW has the potential to meet human needs, including sanitation and food security, while protecting the environment. We use an interdisciplinary case study approach including systems thinking to assess Sri Lanka’s national MSW composting system, which primarily receives residential and commercial food waste. We embed quantitative compost quality analysis and interviews at 20 composting facilities within a broader qualitative assessment informed by ~60 stakeholders in total. This approach yields insights on how institutional, economic, social, and biophysical aspects of the system are interrelated, and how challenges and solutions can create undesirable and desirable cascading effects, respectively. Such dynamics can create risks of composting facility failure and unintended consequences, diminishing the chances of achieving a sustainable circular food–nutrient system. Compost quality, which was variable, plays a pivotal role within the system—a function of program design and implementation, as well as a determinant of value capture in a circular economy. We make several recommendations to inform future efforts to sustainably manage biodegradable MSW using composting, drawing on our case study of Sri Lanka and prior case studies from other nations. Key among these is the need for increased emphasis on compost product quality and markets in policy and program design and implementation. Targeted measures are needed to improve waste separation, boost compost quality, effectively use compost standards, encourage compost market development, ringfence the revenues generated at municipal compost plants, and identify efficient modes of compost distribution. Such measures require adequate space and infrastructure for composting, resource investment, local expertise to guide effective system management, strong links with the agriculture sector, and continued political support.